Editorial - Competency-Based Medical Education:Myths And Truths Cbme: Myths And Truths (Indian Journal of Applied-Basic Medical Sciences, 2022)
Competency based medical education• Focus of curriculum: Competencies are clearly defined and thatneeds to be achieved at the end of training.• Structure and content of curriculum: CBME is paced.• Goal: Knowledge application.• Learning style: Teachers and learners are both equally involved.• Logistics of training Implementation: CBME it is not time bound.• Assessment: Assessment is based on Formative assessment,feedback and is criterion referenced. Assessment is by multiple tools,multiple assessors, multiple times, longitudinal and frequent. Lot ofemphasis is on authentic work-based assessment under directobservation.